Enhancing Occupational Safety in Welding: Identifying Hazards and Improving Personal Protective Equipment Utilization Through Hierarchical Task Analysis. - Khorshidikia, Samane; Rismanchian, Masoud; Popov, Georgi; Habibi, Ehsanollah (Journal of Health Scope, 2026)
Background: Welding processes expose workers to a range of occupational hazards, including chemical pollutants, noise, and non-ionizing radiation, which can compromise health. Effective selection and consistent use of personal protective equipment (PPE), along with engineering and management controls, are essential for mitigating these risks. Objectives: The present study aimed to identify occupational hazards in welding operations and propose strategies to enhance worker safety and health through optimized PPE use and workplace risk management. Methods: Hierarchical task analysis (HTA) was applied to systematically decompose the tasks of argon arc welding (TIG) and submerged arc welding (SAW). Other roles and activities within the workshop were examined to assess potential cross-exposures. Workplace hazards were evaluated using a combined qualitative and quantitative approach, including field observations, interviews with workers and technical experts, and analysis of technical and safety documentation. Environmental measurements included noise, airborne pollutants, and radiation levels. Results: The HTA identified multiple stages in welding processes where workers are exposed to hazards such as metal fumes, hazardous chemicals, noise, non-ionizing radiation, and molten metal spatter. Noise levels frequently exceeded recommended limits, while elevated concentrations of manganese and crystalline silica fumes were detected. Shared workspaces led to secondary exposure to hazards from adjacent tasks. Proper use of PPE, including hearing protection, respiratory masks, flame-resistant clothing, and welding helmets, was shown to effectively mitigate these risks. Conclusions: Welding hazards are cumulative and influenced by both task-specific and environmental factors. Continuous and correct use of PPE, combined with engineering controls and management measures such as task rotation, is critical to protect workers' health. Ongoing training, supervision, and workplace monitoring are recommended to ensure compliance and reduce occupational risks in welding environments.